Zoning System and Religious Character of 10th-Grade Students (Phenomenological Study in SMA Negeri 2 Ungaran) - Rangga Ardani; Ida Zahara Adibah; Isnaini (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to examine how SMA Negeri 2 Ungaran implements the zoning system and the New Student Admission System (SPMB) with various challenges and the role of Islamic education in responding to the existing issues. The method used in this study was a qualitative approach with a phenomenological method. Data were collected through observation, interviews, and documentation with the subjects of the study, including 10th-grade students as the main respondents, an Islamic Religious Education teacher, and the SPMB committee as reinforcement. Data analysis was conducted by data collection, data analysis, reduction, and presentation based on Miles and Huberman's theory. In its implementation, the zoning system runs optimally following the technical instructions from the Education Office of Central Java, although facing several insignificant constraints. Based on the students' real experiences, the existing diversity becomes an encouragement of the social adaptation process and strengthens a tolerant attitude and religious discipline. Islamic Religious Education learning that is adaptive, humanistic, inclusive, and emphasizes religious character values, such as love for the environment, tolerance, friendship, anti-bullying, love of peace, strong determination, and social concern can be developed sustainably.